(untitled) (Herald of Journalism, 2016)
In this article the author considers the effect of PR and work of press service of BTA Bank in Kazakhstan. Particular attention is allocated to that BTA Bank has a high quality PR service through which became famous. It is emphasized that BTA Bank since its founding has achieved different high- level ratings. The author in article specifies that specialists of bank in PR – service are engaged in strengthening of the relations with mass media and other works.